Adherence, Mental Health and Illness Perceptions in Autoimmune Liver Disease: Looking Beyond Liver Function Tests. Issue 3 (12th September 2021) - Hames, Anna; Matcham, Faith; Makin, Isobel; Day, Jemma; Joshi, Deepak; Samyn, Marianne
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Objectives: Autoimmune liver disease is commonly diagnosed during adolescence; a period associated with a higher prevalence of non-adherence, mental health concerns and worse health outcomes. The aim of the study was to explore adherence patterns, mental health and illness perceptions in young people with autoimmune liver disease. Methods: Young people with autoimmune liver disease attending a multidisciplinary young adult clinic (16–25 years) completed an electronically administered questionnaire battery. Demographics and disease-related data were collected. Results: Sixty-eight (37 female), median age 17.9 (range 15–22) years completed the screening. Only 51.5% of patients were in remission (aspartate and alanine aminotransferase <36 IU//l) whereas 73% self-reported their adherence >80%. Compared to patients in remission, those not in remission required more immunosuppression, were more depressed and worried but reported a better understanding of their illness. A small but significant correlation was found between aspartate aminotransferase/alanine aminotransferase and adherence percentage ( r = −0.27, P < 0.05 and r = −0.29, P < 0.05 respectively). Age was inversely associated with adherence ( r = −0.31, P < 0.05), and older patients were more worried ( r = 0.44, P < 0.001) and emotionally affected by the condition ( r = 0.32, P < 0.01). Adherence behaviours such as forgetting to take medications (63%), taking medications more frequently before attending appointments (44%) and not having a routine for medications (31%) were prevalent, 7% reported intentional non-adherence. Conclusion: Sup-optimal adherence to treatment is common in young people with autoimmune liver disease and associated with mental health problems and certain illness perceptions. Routine exploration of adherence beliefs and barriers to adherence in a non-judgmental, collaborative way is essential to improve outcome in this vulnerable population.